2007
DOI: 10.3141/1996-05
|View full text |Cite
|
Sign up to set email alerts
|

Public-Private Partnerships in Highways in Transition Economies

Abstract: In many countries the private sector has been involved in financing infrastructure through concessions under a public-private partnership (PPP) program. PPP projects, however, are somewhat underutilized in countries with transition economies, where financing gaps are significant and growing, and there seems to be enormous potential for more private-sector involvement in the financing and operation of highway assets in such countries. The reasons for the low rate of private financing of roads in transition econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 1 publication
0
18
0
2
Order By: Relevance
“…In transition countries, despite the apparently enormous potential for private involvement in the financing and operation of hard infrastructure, the actual application of PPPs has been slow and limited. Queiroz () attributes this phenomenon to the lack of an appropriate legal framework, economic and political instability, and, consequently, high perceived risk. Some scholars have concluded that PPP development in transition countries requires rapid development in procedures, market awareness, institutional acceptance, and risk taking (Snelson ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In transition countries, despite the apparently enormous potential for private involvement in the financing and operation of hard infrastructure, the actual application of PPPs has been slow and limited. Queiroz () attributes this phenomenon to the lack of an appropriate legal framework, economic and political instability, and, consequently, high perceived risk. Some scholars have concluded that PPP development in transition countries requires rapid development in procedures, market awareness, institutional acceptance, and risk taking (Snelson ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…identification, assessment and allocation) reports findings concerning mature PPP markets. The analysis of case studies, usually on a national level has been seen by academia and development institutions (Songer et al, 1997;Lam, 1999;Spackman, 2002;Thomas et al, 2003;de Lemos et al, 2004;Queiroz, 2005;PPIAF, 2006;Singh and Kalidindi, 2006;Ng and Loosemore, 2007 and others) as a means to assist in PPP success by presenting the most pronounced risks and best practices in risk allocation.…”
Section: Introductionmentioning
confidence: 98%
“…All other things being equal, this rate depends largely on the construction cost and traffic volumes (Queiroz 2007). Estimating such toll rates for different PPP projects can be largely facilitated when an appropriate financial tool is available.…”
Section: Estimating Minimum Toll Ratesmentioning
confidence: 99%